Expedient Synthesis of Bridged Bicyclic Nitrogen Scaffolds via Orthogonal Tandem Catalysis. Issue 40 (11th August 2021) - Biswas, Sovan; Van Steijvoort, Ben F.; Waeterschoot, Marjo; Bheemireddy, Narendraprasad Reddy; Evano, Gwilherm; Maes, Bert U. W.
Abstract: Bridged nitrogen bicyclic skeletons have been accessed via unprecedented site‐ and diastereoselective orthogonal tandem catalysis from readily accessible reactants in a step economic manner. Directed Pd‐catalyzed γ‐C(sp 3 )‐H olefination of aminocyclohexane with gem‐dibromoalkenes, followed by a consecutive intramolecular Cu‐catalyzed amidation of the 1‐bromo‐1‐alkenylated product delivers the interesting normorphan skeleton. The tandem protocol can be applied on substituted aminocyclohexanes and aminoheterocycles, easily providing access to the corresponding substituted, aza‐ and oxa‐analogues. The Cu catalyst of the Ullmann‐Goldberg reaction additionally avoids off‐cycle Pd catalyst scavenging by alkenylated reaction product. The picolinamide directing group stabilizes the enamine of the 7‐alkylidenenormorphan, allowing further product post functionalizations. Without Cu catalyst, regio‐ and diastereoselective Pd‐catalyzed γ‐C(sp 3 )‐H olefination is achieved. Abstract : Bridged bicyclic nitrogen scaffolds are conformationally restricted analogues of important aminocarbo‐ and aminoheterocycles. Fixation of functional groups in a biologically active conformation provides efficient and selective ligands for various targets, featuring improved ADME parameters. Long synthetic sequences relying on traditional organic chemistry currently limit the drug discovery process. New step‐economic synthetic procedures are therefore highly sought after.